Avaliação da qualidade de vida de profissionais de enfermagem de um hospital geral do Sul de Minas Gerais - Palmiéri, Patrícia De Cássia Ruela (2013)
This is a quantitative, descriptive-analytical and cross-cut research with the aim of evaluating the life quality (LQ) of nursing professionals in a midsize general hospital of a city in the southern state of Minas Gerais, Brazil. It was approved by the Research Ethics Committee of the UNIFAL-MG, Protocol 164/2011. The participants in this study were 07 nursing assistants, 84 nursing technicians and 15 nurses, what amounts to 106 nursing professionals of this institution. Data collection was conducted from May to July 2012. Life quality was assessed by questionnaire of World Health Organization Quality of Life-BREF (WHOQOL-BREF). To characterize socioeconomic features and labor we used a semi-structured questionnaire and data were tabulated using the BrOffice Calc and statistical analysis were performed in R software. It was applied a test of internal consistency to the instrument by Cronbach’s Alpha Coefficient. Descriptive statistics were applied to associations between variables, and General LQ and domains. Besides the U tests of Wilcoxon-Mann-Whitney, Kruskal-Wallis and p-value 0.05% significance level. There was a predominance of females – 76.42% (81 women); aged 21 to 40 years were 63.21% (67) and 32.07% (34) over 40 years. All professed a religious faith with a predominance of the Catholic religion – 74.53% (79). The educational level was that 76.42% (81) have completed high school and 16.98% (18) have degree. Individual income to 58.50% (62) equaled up to two minimum wages and household income to 61.32% (65) from 2 to 4 minimum wages. 51.89% (55) of respondents have a companion and two or more children 47.17% (50). There are 38% (40) who have other jobs. The length of service in the institution of 1 to 10 years amounts to 53.77% (57) and length of employment 1-10 years is in the range of 51.89% (55). The mean score obtained in assessing the overall quality of life was 69.69; 65.59 in the physical domain, 65.72 in the psychological domain, 65.33 in social relationships domain and 59.19 in the environment domain. In the associations of socioeconomic variables and labor with the general quality of life and the quality of life domains there was significant difference for degree training with LQ General; personal income and family income in relation to the social relationships domain and professional category with General LQ. The Cronbach’s Alpha General Coefficient of WHOQOL-BREF applied in this study was 0.77, which is considered satisfactory. However, with regard to the General LQ and the domains of WHOQOL-BREF values were low. We conclude that these professionals, mostly, are satisfied in life and at work. However, some issues deserve to be highlighted in order to solve some problems that although discreet can become incisive, proposing intervention actions for the institution in promoting the quality of life of these professionals.